Analisis Fundamental Variabel Makroekonomi Terhadap Pertumbuhan Ekonomi Negara Maju Asia - rahmawati, pipit dwi; Susilowati, Dwi; Sari, Novi Primita (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
This research examines economic growth patterns in developed Asian countries during the 2014-2023 period. Employing a quantitative method based on secondary data, this study applies panel data analysis that combines cross-sectional information from six developed Asian countries (namely Japan, Korea, Singapore, Hong Kong, Macau, and Israel) along with time series data spanning ten years. Data collection was carried out through a series of steps including tracking, categorization, and documentation sourced from the World Bank database. Data processing utilized Panel Data Regression techniques executed through the Eviews-12 program, with Fixed Effect (FE) selected as the most appropriate model. The research findings reveal two distinct patterns: exchange rates and imports had significant negative effects on economic growth, while exports contributed significantly positive effects to economic growth across the five developed Asian countries during the study period. Statistical calculations through the regression model indicate optimal reliability, as evidenced by an R-Square value of 0.998185.